Progressive Muslim Intellectual as The Basic Concepts of New Paradigm on Integration Islam and Science Education - Dartim Ibnu Rushd; Mohamad Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The background of this research is that there is still a lack of references on the integration of knowledge or